2011
DOI: 10.1371/journal.pone.0018735
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Immunomodulation of Human Dendritic Cells by the Probiotic Lactobacillus rhamnosus Lcr35

Abstract: The response of the immune system to probiotics remains controversial. Some strains modulate the cytokine production of dendritic cells (DCs) in vitro and induce a regulatory response, while others induce conversely a pro-inflammatory response. These strain-dependent effects are thought to be linked to specific interactions between bacteria and pattern recognition receptors. We investigated the effects of a well characterized probiotic strain, Lactobacillus rhamnosus Lcr35, on human monocyte-derived immature D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
62
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 47 publications
12
62
1
Order By: Relevance
“…Previously, we have shown that pretreatment of piglets with L. rhamnosus increases in the number of lactobacilli and bifidobacteria accompanied by a reduction in coliform shedding in feces by day 9 (i.e., 24 h after F4 ϩ ETEC challenge) (22). Similarly, the probiotic L. rhamnosus strain Lcr35 was shown to induce a strong dose-dependent increase in the production of pro-Th1/Th17 cytokines by human dendritic cells (32). The serum concentration of IL-10 changed in a similar manner to that of IL-17A in our experiments, although the changes were not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we have shown that pretreatment of piglets with L. rhamnosus increases in the number of lactobacilli and bifidobacteria accompanied by a reduction in coliform shedding in feces by day 9 (i.e., 24 h after F4 ϩ ETEC challenge) (22). Similarly, the probiotic L. rhamnosus strain Lcr35 was shown to induce a strong dose-dependent increase in the production of pro-Th1/Th17 cytokines by human dendritic cells (32). The serum concentration of IL-10 changed in a similar manner to that of IL-17A in our experiments, although the changes were not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…LTA also stimulated macro- site effect in the case of use of Bifidobacterium bacteria [28]. Evrard et al showed that L. rhamnosus Lcr35 increased synthesis of the Th1/Th17 cytokine profile, but had no significant effect on the level of IL-10 [29]. Previously, we have demonstrated the impact of EPS 37 on humoral immune response in mice.…”
Section: Discussionmentioning
confidence: 78%
“…Some strains modulate the cytokine production in vitro and induce a regulatory response, whereas others induce a pro-inflammatory response (Evrard et al 2011). However, several studies have provided unequivocal evidence that the specific strains of probiotics are able to stimulate multiple aspects of innate immunity (Weiss et al 2010) as well as to increase the humoral immunity (Roberfroid 2002).…”
Section: Discussionmentioning
confidence: 99%